2015
DOI: 10.4236/oalib.1101947
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Tuberculosis Diagnosis among Tuberculosis Patients at the Three Hospitals: Asella, Robe and Abomsa of Arsi Zone, Oromia Regional State, March, 2015

Abstract: Background: Tuberculosis (TB) remains a major global health problem. Delay in tuberculosis diagnosis may worsen the disease and increase transmission within the general population. This study estimated the prevalence of diagnosis delay and its determinants. Objective: To measure the magnitude of patient and health service delay and identify the factors associated with the delay. Methodology: A facility based cross-sectional study design was conducted at the three hospitals of Arsi Zone from December 2014-March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
24
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 25 publications
13
24
6
Order By: Relevance
“…The observed median total delay in our study is lower than that reported from an earlier study conducted in a comparable setting in the Amhara Region of Ethiopia [ 5 ], but higher than the study findings reported from other regions of Ethiopia [ 7 , 9 , 19 ]. It is also higher compared to the studies done in Nepal [ 21 ], Angola [ 39 ], Zimbabwe [ 40 ] and South Africa [ 41 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The observed median total delay in our study is lower than that reported from an earlier study conducted in a comparable setting in the Amhara Region of Ethiopia [ 5 ], but higher than the study findings reported from other regions of Ethiopia [ 7 , 9 , 19 ]. It is also higher compared to the studies done in Nepal [ 21 ], Angola [ 39 ], Zimbabwe [ 40 ] and South Africa [ 41 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Patients with total delay of > 60 days were found to be more likely to have unfavorable treatment outcome than patients with total delay of ≤ 60 days. Long delays in diagnosis and treatment start contribute to severity and complications of illness that may result in poor treatment outcomes [ 19 , 20 ]. It also increases the risk of developing anti-TB drug resistance leading to increased mortality rate, treatment failure and transmission of drug resistant TB strains in the community [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…e finding is similar to some studies conducted in Ethiopia which reported median of 30 days [9,25]. On the contrary it was lower than other local studies that showed a median of 56 days [15], 40 days in Arsi Zone [16], 60 days in Bahirdar [17], 70.5 days in Afar [18] and also elsewhere, 50 days in Nepal [19]. is may be explained by the difference in access to health service and quality of services; these studies were conducted in the rural parts of Ethiopia where health seeking behaviour and access are likely to be low.…”
Section: Discussionsupporting
confidence: 88%
“…Poor knowledge of TB is associated with patient delay. The association between poor knowledge of TB and patient delay is very strong as is also the case in other studies from Bahir Dar, Tigray, Somali and Uganda [20,22], [23,24]. Financial constraints for transportation were associated with patient delay in this study.…”
Section: Discussionsupporting
confidence: 82%